2007
DOI: 10.1002/art.22867
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling antagonists are potential prognostic biomarkers for the progression of radiographic hip osteoarthritis in elderly Caucasian women

Abstract: Objective. To determine whether serum levels of 2 Wnt signaling antagonists, Frizzled-related protein (FRP) and Dkk-1, are associated with the development and progression of radiographic hip osteoarthritis (RHOA).Methods. Pelvic radiographs were obtained a mean of 8.3 years apart in 5,928 Caucasian women >65 years of age who were enrolled in the Study of Osteoporotic Fractures. Random sampling of this cohort was performed, with ϳ180 subjects per group assigned to 2 nested case-control studies on RHOA incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 32 publications
5
76
1
3
Order By: Relevance
“…However, its function in OA cartilage destruction is a subject of controversy. For instance, a cohort study suggested a positive correlation between serum levels of Dkk-1 and reduced progression of radiographic hip OA (15,16). In addition, investigators in another study reported that circulating Dkk-1 levels In B and D, ‫ء‬ ϭ P ϭ 0.05; ‫ءء‬ ϭ P ϭ 0.005; ‫ءءء‬ ϭ P ϭ 0.0001, by analysis of variance followed by post hoc test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its function in OA cartilage destruction is a subject of controversy. For instance, a cohort study suggested a positive correlation between serum levels of Dkk-1 and reduced progression of radiographic hip OA (15,16). In addition, investigators in another study reported that circulating Dkk-1 levels In B and D, ‫ء‬ ϭ P ϭ 0.05; ‫ءء‬ ϭ P ϭ 0.005; ‫ءءء‬ ϭ P ϭ 0.0001, by analysis of variance followed by post hoc test.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cohort studies indicated that high serum levels of Dkk-1 were associated with reduced progression of radiographic hip OA (15,16). Additionally, a recent study by Honsawek et al (17) indicated that plasma and synovial fluid levels of Dkk-1 were markedly lower in the knees of OA patients than in those of healthy controls, suggesting that circulating Dkk-1 levels were inversely correlated with radiographic OA severity.…”
mentioning
confidence: 99%
“…It is reported that alterations of circulating DKK-1 protein levels have been shown to be associated with various diseases such as multiple myeloma, rheumatoid arthritis, breast cancer, lung cancer, and esophageal cancer patients. [12][13][14][15][16] However, there is no documented study to associate circulating DKK-1 levels with DR. There is also no information available concerning the DKK-1 level in the vitreous fluid.…”
Section: Discussionmentioning
confidence: 99%
“…11 DKK-1 is a secreted protein and readily detectable in the circulation. [12][13][14][15][16] Therefore, it is hypothesized that DKK-1 levels in circulation or ocular fluid could be associated with the development and progression of DR.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven ''progression'' studies [7-9, 15, 17, 24, 29, 30, 35, 37, 39] investigated the association of 13 different biomarker levels with the progression of hip OA. Of the 11 studies, four looked at progression of known hip OA [9,15,37,39]; three studies investigated the progression to incident hip OA from unspecified prearthritic hip disease [8,17,29]; and four studies investigated both OA progression and incidence [7,24,30,35]. Duration of followup to evaluate OA progression ranged from 1 year to 15 years.…”
Section: Literature Searchmentioning
confidence: 99%